Great expectations: Reservation wages and the minimum wage reform - Alexandra Fedorets; Alexey Filatov; Cortnie Shupe (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
We use the German Socio-Economic Panel to show that introducing a high-impact statutory minimum wage causes an increase in reservation wages of approximately 4 percent at the low end of the distribution. The shifts in reservation wages and observed wages due to the minimum wage reform are comparable in their magnitude. Additional results show that German citizens adjust their reservation wages more than immigrants. Moreover, suggestive evidence points to a compensation mechanism in which immigrants trade wage growth against job security.
Keywords: J22; J3; 330; minimum wage; reservation wage; labor supply